The Influence of the Global Financial Crisis on the Chinese Art Market - Piechaczek, Anna (Chiński rynek sztuki a globalny kryzys finansowy, 2010)
Investment in art is not considered the mainstream asset class. Art is incorporated into portfolios to diversify them. The art market seems to be less subject to macroeconomic aspects than other investment areas and during turbulences on the stock exchange some investors decide to use alternative forms of capital allocation (including investments in paintings and sculptures). However, the art market suffers adverse consequences of the global financial crash as well, which can be easily observed in particular on the emerging art markets. The purpose of this paper is to show how the financial crisis influences the major emerging art market which is the Chinese art market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 109-120
Keywords: Chinese art market; global economic crisis; art investments; art finance